(BI)LITERACY AND EMPOWERMENT: EDUCATION FOR INDIGENOUS GROUP IN BRAZIL (Polifonia, 1993)
ABSTRACT: This paper examines the history of language policy in brazil, the question of a national language, and their effect on indigenous language education projects, specifically bilingual education. Independent "Freirean" educational projects are analysed according to the standard models of bilingual education transitional, maintenance, and enrichment. a case is made that the goals os these projects might ultimately be more assimilationist than pluralistic.